2017
DOI: 10.1016/j.otsr.2016.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Cementless lateralized stems in primary THA: Mid-term survival and risk factors for failure in 172 stems

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…The Matlab (version 2014b, Mathworks, USA) script used to automate the implant sizing and alignment predicted a median size that match previous reports (size 12 for standard offset Corail ® and size 11 for lateralised counter designs) in a retrospective study on 172 stems [18]. The micromotion values predicted in this study were also in agreement with those reported in previous in-silico literature on cementless implant primary stability (Peak = 20 -356 μm) [25][26][27][43][44][45][46][47].…”
Section: Accepted Manuscriptsupporting
confidence: 87%
See 2 more Smart Citations
“…The Matlab (version 2014b, Mathworks, USA) script used to automate the implant sizing and alignment predicted a median size that match previous reports (size 12 for standard offset Corail ® and size 11 for lateralised counter designs) in a retrospective study on 172 stems [18]. The micromotion values predicted in this study were also in agreement with those reported in previous in-silico literature on cementless implant primary stability (Peak = 20 -356 μm) [25][26][27][43][44][45][46][47].…”
Section: Accepted Manuscriptsupporting
confidence: 87%
“…The purpose of this study was to investigate, across a diverse cohort of femora (representative of a broad range of age, age, body mass and stature), the influence of restoring the femoral offset on the primary stability of cementless femoral stems, using a range of stem lateralisation options. For this study, the Corail® femoral stem (DePuy Synthes, Warsaw, USA) was selected as it is available with different offsets, with documented clinical history for all of the design options [17,18,[32][33][34][35]. Subject-specific FE modelling was used in this study to evaluate the primary stability of the different lateralisation options for the Corail® stem in a diverse cohort of femora for two of the most commonly encountered daily activities; level gait and stair climb activities.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…One question that may arise is whether lateralised stems could be used during BHA due to femoral neck fracture and what the survival of high offset Reumatologia 2022; 60/5 stems would be in such patients. Some studies analysing the survivorship of high offset stems suggest that lateralized stems have shorter survival periods than standard stems [18,19] or that high offset stems have a high risk of loosening and surgery failure [20].…”
Section: Discussionmentioning
confidence: 99%
“…Only standard Corail stems were included as lateralised stems previously demonstrated a higher risk of loosening [18,19].…”
mentioning
confidence: 99%